2017
DOI: 10.1002/pros.23440
|View full text |Cite
|
Sign up to set email alerts
|

Altered mitochondrial genome content signals worse pathology and prognosis in prostate cancer

Abstract: Background Mitochondrial genome (mtDNA) content is depleted in many cancers. In prostate cancer, there is intra‐glandular as well as inter‐patient mtDNA copy number variation. In this study, we determine if mtDNA content can be used as a predictor for prostate cancer staging and outcomes. Methods Fresh prostate cancer biopsies from 115 patients were obtained at time of surgery. All cores underwent pathological review, followed by isolation of cancer and normal tissue. DNA was extracted and qPCR performed to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
(68 reference statements)
1
14
0
Order By: Relevance
“…To evaluate a correlation of clinical parameters and mtDNA mutation frequency a logistic regression analysis was performed (Supplementary Table 3). Overall mtDNA mutation load correlated significantly with increasing patient age (p = 0.04, likelihood-ratio test), in line with recent reports 9,20,21 and with lower free to total PSA ratios (fPSA%, p = 0.05, likelihood-ratio test, Supplementary Table 3). A low fPSA% value is a prognostic indicator of poor prognosis 22 .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…To evaluate a correlation of clinical parameters and mtDNA mutation frequency a logistic regression analysis was performed (Supplementary Table 3). Overall mtDNA mutation load correlated significantly with increasing patient age (p = 0.04, likelihood-ratio test), in line with recent reports 9,20,21 and with lower free to total PSA ratios (fPSA%, p = 0.05, likelihood-ratio test, Supplementary Table 3). A low fPSA% value is a prognostic indicator of poor prognosis 22 .…”
Section: Resultssupporting
confidence: 88%
“…Deleterious mtDNA mutation load and OXPHOS capacity. While increasing numbers of potentially deleterious mtDNA mutations in cancer samples are reported [9][10][11][12]21,23 , their functional significance is rarely evaluated. We correlated the frequency and type of mtDNA mutations with functional data for each sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, low mtDNA content was more prevalent in patients who received preoperative radiation therapy, which may be explained by the radiationinduced DNA damage in the mitochondrial genome combined by impaired enzyme synthesis. Although most studies revealed that high mtDNA content was associated with better outcome in cancer, some studies showed contrary data (18,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Thus, the role of mtDNA in cancer prognosis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In human cells, mitochondrial ribosomes synthesize proteins encoded by 13 mitochondrial DNAencoded genes. Recent studies suggested reduced mitochondrial DNA content in PCa [60,61], so it is possible that PCa cells overexpress mitochondrial ribosomes to compensate the decrease of mitochondrial DNA content.…”
Section: Differentially Expressed Corum Protein Complexesmentioning
confidence: 99%